If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + n = 37 Solving 12 + n = 37 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + n = 37 + -12 Combine like terms: 12 + -12 = 0 0 + n = 37 + -12 n = 37 + -12 Combine like terms: 37 + -12 = 25 n = 25 Simplifying n = 25
| -7y+28=-14 | | (4x+5)+(5x-14)=90 | | 2x-4=-8x-4 | | 9+2c=17 | | x=1.5+-0.5y | | 8(x+6)=-24 | | 4(-3x+6)=-13x+8 | | 15+3r-4=1+7r | | 10+2t=18 | | (4n+11)+2(4n+11)=195 | | -15v-40=2-8v | | d/1.2=6 | | 6x-24=-12 | | -18x^4-57x^3+10x^2=0 | | 30=t/7 | | -6x-8+4x=-7x-2 | | -5-8-56n=-8 | | 18=4v+2 | | 5.2a+13=70.2 | | -3x+6=-4x-6 | | 11+3x=170 | | 8z^2-36z+36=20 | | 9x^2=10x | | -7f+10w= | | 4y-13=59 | | 3-a=18 | | 16=2z+4 | | 2y=2y(y-1) | | -5(x-4)=-6(x+8) | | 2y+-3=50 | | 16+2n=-58 | | 9x-32=-5x+52 |